2016
DOI: 10.1016/j.jalz.2016.06.2364
|View full text |Cite
|
Sign up to set email alerts
|

Associations of neighborhood environment with brain imaging outcomes in the Australian Imaging, Biomarkers and Lifestyle cohort

Abstract: These findings indicate associations between neighborhood walkability and brain imaging measures (especially in APOE ε4 carriers) minimally attributable to physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…Therefore, we could assume that there is more room for PA to counterbalance early neuropathological signs within this group. This is consistent with previous studies that demonstrate the effect of PA on brain pathology is most predominant among ε4 carriers (7,47,48).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, we could assume that there is more room for PA to counterbalance early neuropathological signs within this group. This is consistent with previous studies that demonstrate the effect of PA on brain pathology is most predominant among ε4 carriers (7,47,48).…”
Section: Discussionsupporting
confidence: 93%
“…in 60-80% of AD cases and is linked to a 3.2-fold increased AD risk in heterozygosis and up to 14.9fold increased AD risk in homozygosis (5). While most studies claim that PA-protective effects mainly manifest among ε4 carriers (6,7), others identified this same effect exists only in non-carriers (8,9), while other studies report benefits regardless of APOE ε4 allele carriage (10,11). This inconsistent literature is likely due to the use of varying study designs and outcome measures (i.e.…”
mentioning
confidence: 99%
“…With regard to brain health, a previous study of 127 community dwellers was powered to detect associations between environmental attributes and 1.5-year changes in brain volume. 21 However, the participants were on average 10 years older than the iMAP sample. Also, significant 1.5year changes on 6 out of 12 cognitive function measures were detected in 685 cognitively intact participants with a mean age of 67 years (projected average age in iMAP: 65 years).…”
Section: Patient and Public Involvementmentioning
confidence: 88%
“…These samples sizes will, respectively, achieve 80% power to detect effect sizes equivalent to 1.9% and 0.6% of variance explained in longitudinal analyses. With regard to MRI brain imaging outcomes, our study indicated that environmental attributes may explain ~5% of the variance in MRI brain volumetric measures, 21 requiring 152 participants to achieve 80% power in site-specific cross-sectional regression analyses. With a conservative 20% drop-out rate 49 and 200 participants at baseline, the final sample size of 160 participants per site and 560 in total will, respectively, be able to detect effect sizes equivalent to 5.0% and 1.4% of variance explained in longitudinal analyses.…”
Section: Participant Selection and Recruitmentmentioning
confidence: 94%
See 1 more Smart Citation